Investigation of machining performance of lead-free brass materials forged in different conditions after cooling with liquid nitrogen - KAYNAK, YUSUF (My University, 2023)
The forging process, which is one of the hot forming methods, is used to produce plumbing systems, valves, batteries, fittings, condensers, pipes, etc. from brass alloys in duplex structures. Compared to leaded brasses, machining becomes very difficult due to reasons such as long and continuous chips, burrs, built-up edge in the tool, and unacceptable surface quality problems. In this study, studies have been carried out to improve the machining process that minimizes the mentioned machining problems by controlling the microstructural of lead-free brass materials. Therefore, by examining the effect of the copper content of the forged material, forging temperature, the cryogenic cooling method input parameters after forging on the phase ratio of the material, investigations were carried out on obtaining a high-performance machining process close to the machinability performance of leaded brass materials with good chip breakability. The change in the distribution of beta phases in the material after forging was investigated and machining tests were performed as a hole drilling operation. Cutting forces, surface roughness, and dimensional accuracy analyzes were evaluated within this purpose. The relationship between the beta phase ratio in the material and the machinability has been revealed and it has been observed that the CW511L alloy produced in three different ratios in the standard range and although they are the same material, the Cu% ratio causes significant changes in terms of machinability.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; Cryogenic Cooling; Hot Forging; Lead-Free Brass; Machining; Microstructure